Electronic Communications Systems : Fundamentlas through Advanced - Tomasi, Wayne (New Delhi Pearson India, 2009)
omprehensive in scope and contemporary in coverage, this text introduces basic electronic and data communications fundamentals, and explores their application in modern digital and data communications systems. Students with previous knowledge in basic electronic principles and fundamental calculus concepts will gain a complete understanding of the topics presented here. Tomasi's Advanced Electronic Communications Systems 6/e is the last 10 chapters of this text.
Appendix A 1065-1082p.; Index 1093-1115p.; Reprint 2013.
Keywords: Digital transmission; Satellite communications; Telephone circuit; Amplitude modulation